2000
DOI: 10.1556/avet.48.2000.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta-carotene and nucleotide base supplementation on blood composition and immune response in weaned pigs

Abstract: The effect of synthetic beta-carotene and synthetic nucleotide base on daily weight gain, feed consumption and certain haematological, biochemical and immunological parameters of piglets were studied in a 3-week experiment. Beginning one week prior to weaning, the diet fed to one experimental group of piglets was supplemented with 10% Rovimix Beta-carotene at 875 mg/kg of diet. Synthetic uracil and adenine (98%, Sigma-Aldrich) were mixed into the diet of the other experimental group at doses of 500 mg/kg of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
8
2
Order By: Relevance
“…The diets supplemented with nucleotides failed to affect the growth performance of weaned pigs. The results are not associated with the previous report by Zomborszky‐Kovacs et al. (2000).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The diets supplemented with nucleotides failed to affect the growth performance of weaned pigs. The results are not associated with the previous report by Zomborszky‐Kovacs et al. (2000).…”
Section: Discussioncontrasting
confidence: 99%
“…The diets supplemented with nucleotides failed to affect the growth performance of weaned pigs. The results are not associated with the previous report by Zomborszky-Kovacs et al (2000). They have found that the diets supplemented with 0.5% nucleotide base increases the average feed intake and daily gain.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These variations may relate directly to the type and levels of nucleotides supplemented in the diet. Zomborszky-Kovács et al (2000) found that supplementation of the synthetic nucleotide bases adenine and uracil at 0.5 g/kg to weanling pig diets improved growth performance. Sauer et al (2012) found that feeding a mixture of pure nucleotides (5′AMP, 5′CMP, 5′GMP, 5′IMP, and 5′UMP) to weanling pigs increased ADFI but did not improve gain or feed efficiency.…”
Section: Discussionmentioning
confidence: 97%